Collecting patient-reported outcomes via the COTIDIANA smartphone app: a prospective validity study - Daniel Aletaha; Tanja A Stamm; Paul Studenic; Helga Radner; Nadja Kartschmit; Elsa Frãzao-Mateus; Nasim Nakhost Lotfi; Francisco Nunes; Pedro Matias; Ricardo Graca (RMD Open)
Background Self-management of rheumatic and musculoskeletal diseases often involves regular assessments of disease-related outcomes. In recent years, smartphone apps are used to collect electronic patient-reported outcomes (ePROMs), supporting the self-management process and improvement of health-related quality of life. We aimed to assess the reliability and comparability of frequent remote monitoring by using ePROMs via a smartphone.Methods Patients (≥18 years) with Sjögren’s disease (SjD), osteoarthritis (OA) and psoriatic arthritis (PsA) were recruited from our outpatient clinic and asked to complete seven short daily as well as weekly questions (visual analogue scale) on global disease activity (PGA), pain, anxiety and depression, fatigue and sleep) for 14 days. To assess reliability, intraclass correlation (ICC) for 1–6-day test-retest intervals, as well as the smallest detectable difference (SDDs), were calculated. Convergent validity was evaluated via correlation of daily and weekly ePROMs.Results 48 patients (76.12% female: 18 SjD, 20 PsA, 10 OA) were included for analyses. At the 1-day test-retest interval, ICCs ranged between 0.84 and 0.89 and SDDs from 1.04 to 2.10, for all domains. The 6-day interval presented wider reliability with ICCs from 0.23 to 0.73 and SDDs from 1.89 to 2.88. While all measures demonstrated high test-retest reliability during the 1-, 2- and 3-day intervals (ICC: 0.83–0.98), an increase in SDDs and a decrease in ICCs were observed as intervals extended. Daily measured ePROMs highly correlated with its corresponding weekly ePROM (pain=0.97, anxiety and depression=0.94, fatigue=0.90, sleep=0.95, PGA=0.94).Conclusion Reliability was particularly stable at shorter intervals with more variation over time. Convergent validity was high between daily and weekly assessment. Short ePROMs collected via smartphones may offer flexibility to vary assessment times while maintaining consistent reliability.